Temperature Anisotropy Instabilities Stimulated by the Solar Wind Suprathermal Populations - Lazar, Marian; López, R.A.; Shaaban, Shaaban Mohammed; Poedts, Stefaan; Yoon, Peter Haesung; Fichtner, Horst (Frontiers in Astronomy and Space Sciences, 2022)
This review paper compiles recent results obtained by the present group of authors describing the effects of suprathermal populations present in space plasmas (up to a few keVs) on temperature anisotropy instabilities. Of particular interest are the electromagnetic cyclotron and firehose excitations, which play a major role in limiting temperature anisotropy, resulting, for instance, from the adiabatic expansion of the solar wind. Relying on a rigorous modeling and interpretation of the observed velocity distributions, both theoretical models and numerical simulations indicate a systematic stimulation of these excitations in the presence of suprathermal populations of electrons or protons. Moreover, the enhanced fluctuations react back on particles, and determine a faster and deeper relaxation of their anisotropy. The present comparative analysis suggests that previous studies, considering only quasi-thermal low-energy populations, may have significantly underestimated these excitations and their implications in various applications in space plasmas.